Biological indicators of lacustrine and alluvial soils in Venezuela under dif ferent land use. Part 2. Assessment of soil quality - Ruiz-Dager, Magaly; Paolini-Gomez, Jorge Emilio (REVISTA TERRA LATINOAMERICANA, 2022)
The best agricultural soils in Venezuela are located in the Valencia lake basin, but unfortunately for various reasons, such as the use of recycled gray water with or without treatment from urban and industrial origin, they have been subjected to accelerated degradation processes. Detecting the causes of soil deterioration in early stages with biochemical indicators will allow timely corrective measures to be applied. In this work, three suitable measurement tools were adopted with the following mathematical indexes: alteration index (AI3), enzymatic geometric mean and radar diagram area. The quality of the alluvial and lacustrine soils of the lake Valencia basin cultivated with sugar cane and banana was evaluated. The calculation of the indexes was based on the determinations of dehydrogenase, arginine ammonif ication, acid phosphomonoesterase, alkaline phosphomonoesterase, β-glucosidase, urease and protease activities. The estimated quality indexes showed that agricultural use causes a disturbance of the natural balance, the order being: natural vegetation> sugar cane> banana. The alteration index (AI3) and the enzyme geometric mean (MGe) correlated signif icantly with the metabolic ef f iciency quotient. The radar plots for each soil type (lacustrine and alluvial) under both types of land use (sugar cane and banana) conf irmed the results of the other indexes. Soils planted with both crops showed a lower quality compared to the reference soils under native vegetation.